Comparative study between manual therapy and TENS Burst in patients with tension-type cephalalgia - Denise Vasconcelos Fernandes; Fhelício Sampaio Viana; Jefferson Paixão Cardoso
Introduction Cephalgia or cephalalgia is one of the most common symptoms in the general population. Objective To compare the efficacy of physical therapy modalities, through manual therapy and the effect of Transcutaneous Nerve Stimulation (TENS) for tension-type cephalalgia. Materials and methods The study was compounded by 60 subjects, but only 40 of them completed it, due to the exclusion criteria. These were divided into control group and intervention group. The control group received treatment - manual therapy. The intervention group received TENS Burst. Patients underwent ten sessions of treatment, made at every two days on a week, lasting 30 minutes each session. Results The characteristics related to lifestyle, postural issues and range of motion are responsible for the main causes of tension-type cephalalgia. Discussion treatments showed effective results in all cases in relation to pain intensity, but the use of manual therapy techniques give the patient a better quality of life compared to the use of TENS. Final considerations The treatment of this condition deserves analysis and studies; however, there are only a few studying physical therapy techniques, especially regarding to the use of TENS.